PENGARUH KEPEMIMPINAN, PENDIDIKAN DAN PELATIHAN MOTIVASI KERJA, DAN BUDAYA ORGANISASI TERHADAP KOMPETENSI DAN KINERJA GURU - Meita Pragiwani Soetopo Soetopo (Jurnal Ekonomi, 2016)
The purpose of this study was to determine and assess and analyze the effects of transformational leadership, education and training, work motivation, and organizational culture on teacher competence and its implications on teacher performance.This study uses the approach of human resources management science are combined with theories of organizational behavior. This type of research is descriptive and explanatory verificative survey by research data cross section where the research was conducted at a specific time period with the unit of analysis is the teachers who teach in the Vocational School Public and Private, with the unit of observation is the Vocational High School in Public and Private Bandung Raya. This study data analysis techniques using the path analisys.The results showed that the competence of teachers either directly or indirectly influenced by the transformational leadership, education and training, motivation to work and organizational culture. This study also shows the influence of teachers on the performance of teacher competency significantly. The results of this study revealed that 1) transformational leadership affects the competence of teachers; 2) education and training of the most dominant influence on the competence of teachers; 3) motivation is a factor that most small influence on teacher competence, 4) organizational culture affect the competence of teachers ; 5) the teacher's performance is significantly affected by the competence of teachers. at the Vocational School Public and Private in Bandung.